Autochthonous and Travel Acquired Hepatitis E Virus in Australia - O’Keefe, Jacinta; Tracy, Lilly; Yuen, Lilly; Bonanzinga, Sara; Li, Xin; Chong, Brian; Nicholson, Suellen; Jackson, Kathy (Frontiers in Microbiology, 2021)
Background: Hepatitis E virus (HEV) is a common cause of acute viral hepatitis with significant morbidity and mortality, particularly in pregnant women. There are four major genotypes which can cause disease in humans. Genotypes 1 and 2 are usually associated with outbreaks and spread via faecal/oral route or contaminated water. Genotypes 3 and 4 are zoonotic and usually associated with handling of pigs or consumption of contaminated pork. The strains circulating in Australia have never been characterised. Rationale/Aims: The aims for this project are to identify the HEV genotypes found in Australia and link them to possible sources of transmission by phylogenetic analysis. Materials and Methods: Between 2015 and 2020, 91 HEV isolates were sequenced and genotyped using an in-house PCR. Sixty-six of these were also sequenced by using the international HEVnet primers. Genotypes were determined using the BLASTn program. Relatedness to other strains in Australia was determined by phylogenetic analyses of the HEVnet sequences. Isolates were also stratified by state of origin, gender, age, predisposing factors and travel history (if known). Results: Of the 91 HEV isolates sequenced, 55 (60.4%) were genotype 1. There were 34 (37.4%) genotype 3 strains and two genotype 4 (2.2%). At least 20 of the genotype 1 strains have been linked to travel in India, and another three with Pakistan. Five of the “Indian” strains were closely related and are suspected to have originated in Gujarat. Phylogenetic analysis also showed that 12 genotype 3 strains were genetically related and potentially acquired in/from New South Wales, Australia. The two genotype 4 strains may have originated in China. Discussion: This is the first study to describe the HEV isolates identified in Australia. The results infer that HEV may be acquired during overseas travel as well as locally, presumably from consumption of pork or pork-related products. The phylogenetic analyses also reveal clusters of infection originating from India and Pakistan. This study provides some insight into the source and epidemiology of HEV infection in Australia which may be used to guide public health procedure and enable the implementation of measures to deal with potential outbreaks of infection.